Генетична трансформація цукрового буряку синтетичним геном cry1C - Курило, В.В.; Ємець, А.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Insect pest’s impact makes a significant limitation of the sugar beet crop yield. Integration of cry-genes of Bacillus thuringiensis into the plant genome is one of the promising strategies to ensure of plant resistance. The aim of this work was to obtain sugar beet lines (based on the MM1/2 line) transformed with cry1C genes using vector construction pRD400-cry1CST. Methods. Genetic transformation of sugar beet was performed using the procedure of co-cultivation of leaf explants with Agrobacterium tumefacins. Results. Sugar beet line MM1/2 was transformed by Agrobacterium-mediated transformation using vector pRD400-cry1CST, containing synthetic cry1C gene and selectable marker gene neomycin phosphotransferase II (nptII), that conferring resistance to kanamycin. After the optimization protocol of genetic transformation and direct regeneration from leaf discs a transgenic sugarbeet lines were obtained. They survived on a selective medium containing 1 mg/l benzylaminopurine (BAP), kanamycin as the selective agent in a concentration of 100 mg/l and 250 mg/l cefotaxime to eliminate excess Agrobacterium. The frequency of transformation in this case was 57.2 %. Conclusions. Based on the selection and capacity for growth and development in the presence of the selective agent kanamycin, we could suggest that a target cry1C gene was integrated into the genome of sugar beet plants, that confers resistance to a number of insect genus of Lepidoptera and Diptera and its expression in transgenic lines of B. vulgaris. Keywords: genetic transformation, Agrobacterium tumefaciens, Beta vulgaris, cry-genes.